Recent Advances of SnO2-Based Sensors for Detecting Volatile Organic Compounds - Li, Baoliang; Zhou, Qu; Peng, Shudi; Liao, Yiming (Frontiers in Chemistry, 2020)
SnO2 based sensors have received extensive attention in the field of toxic gas detection due to their excellent performances with high sensitivity, fast response, long-term stability. Volatile organic compounds (VOCs), originated from industrial production, fuel burning, detergent, adhesives and painting, are poisonous gases with significant effects on air quality and human health. This mini-review focuses on significant improvement of SnO2 based sensors in VOCs detection in recent years. In this review, the improvement strategies of the SnO2 sensor from the perspective of nanomaterials are presented. Furthermore, the sensing performances of these SnO2 nanomaterial sensors in VOCs detection is summarized. Finally, this paper discusses the sensing mechanism of SnO2, and the future development prospect and challenges is proposed.